Speckle tracking as a method to measure hemidiaphragm excursion. Issue 1 (22nd August 2016) - Goutman, Stephen A.; Hamilton, James D.; Swihart, Blake; Foerster, Bradley; Feldman, Eva L.; Rubin, Jonathan M.
ABSTRACT: Introduction: Diaphragm excursion measured via ultrasound may be an important imaging outcome measure of respiratory function. We developed a new method for measuring diaphragm movement and compared it to the more traditional M‐mode method. Methods : Ultrasound images of the right and left hemidiaphragms were collected to compare speckle tracking and M‐mode measurements of diaphragm excursion. Speckle tracking was performed using EchoInsight (Epsilon Imaging, Ann Arbor, Michigan). Results : Six healthy subjects without a history of pulmonary diseases were included in this proof‐of‐concept study. Speckle tracking of the diaphragm is technically possible. Unlike M‐mode, speckle tracking carries the advantage of reliable visualization and measurement of the left hemidiaphragm. Conclusions : Speckle tracking accounted for diaphragm movement simultaneously in the cephalocaudad and mediolateral directions, unlike M‐mode, which is 1‐dimensional. Diaphragm speckle tracking may represent a novel, more robust method for measuring diaphragm excursion, especially for the left hemidiaphragm. Muscle Nerve 55 : 125–127, 2017